Proceedings of the 2019 Conference of the North 2019
DOI: 10.18653/v1/n19-1334
|View full text |Cite
|
Sign up to set email alerts
|

Structural Supervision Improves Learning of Non-Local Grammatical Dependencies

Abstract: State-of-the-art LSTM language models trained on large corpora learn sequential contingencies in impressive detail and have been shown to acquire a number of non-local grammatical dependencies with some success. Here we investigate whether supervision with hierarchical structure enhances learning of a range of grammatical dependencies, a question that has previously been addressed only for subject-verb agreement. Using controlled experimental methods from psycholinguistics, we compare the performance of word-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 22 publications
2
39
1
Order By: Relevance
“…RNNGs are generative models of language that jointly model syntax and surface structure by incrementally generating a syntax tree and sentence. As with NLMs, RNNGs make no independence assumptions, and have been shown to outperform NLMs in terms of perplexity and grammaticality judgment when trained on gold trees (Kuncoro et al, 2018;Wilcox et al, 2019). We take the best run from each model and parse the training set, 15 and use the induced trees to supervise an RNNG for each model using the parameterization from Kim et al (2019).…”
Section: Resultsmentioning
confidence: 99%
“…RNNGs are generative models of language that jointly model syntax and surface structure by incrementally generating a syntax tree and sentence. As with NLMs, RNNGs make no independence assumptions, and have been shown to outperform NLMs in terms of perplexity and grammaticality judgment when trained on gold trees (Kuncoro et al, 2018;Wilcox et al, 2019). We take the best run from each model and parse the training set, 15 and use the induced trees to supervise an RNNG for each model using the parameterization from Kim et al (2019).…”
Section: Resultsmentioning
confidence: 99%
“…Crucially, although islands block the fillers from associating with gaps within the island, they do not prohibit association between fillers and gaps that occur structurally to the right of the island, as shown in Figure 3. Wilcox et al (2019b) found that while large scale models are able to thread the 2 × 2 contingency between fillers and gaps into syntactically complex material-such as through numerous sentential embeddings-they do not thread the dependency into some island configurations. Inside of relative clauses and temporal adjuncts, for example, the presence or absence of an upstream filler has no effect on the relative surprisal of a gap, and the wh-licensing interaction drops to near zero.…”
Section: Licensing Over Syntactic Islandsmentioning
confidence: 98%
“…• Long-Distance Dependencies are covariations between two tokens that span long distances in tree depth. Test suites include Filler-Gap Dependencies (FGD) (6 suites) from and Wilcox et al (2019b), and 2 novel Cleft suites, described in detail below. 1b)) and lexicalized verbs should set up expectations for NPs (the region in bold should have a lower surprisal in (1d) than in (1c)).…”
Section: Syntactic Coveragementioning
confidence: 99%